Improving the Quality of Life for Bipolar Survivors during the Covid-19 Pandemic in the Bipolar Community of Yogyakarta - Andhita Dyorita Khoiryasdien (Peneliti Teknologi Teknik Indonesia, 2021)
The COVID-19 pandemic has lasted more than a year. This of course has an impact on all aspects of people's lives, both economically, socially and educationally. This impact is certainly also felt by people with mental disorders, one of which is Bipolar sufferers. Just like individuals in general, they also experience a difficult adjustment period in dealing with changes during the COVID-19 pandemic. Moreover, psychologically, their mental condition is clearly different from other individuals. Mentally, bipolar survivors are more susceptible to stress and it is feared that they will experience relapses more often during the COVID-19 pandemic, even though they must continue to do activities, work and carry out their respective obligations. Difficulty accessing health facilities and mental health information during this pandemic has also become a problem for bipolar survivors. This community service provides education related to pharmacology, psychological conditions and effective communication with the aim of bipolar survivors having the information provision in carrying out their daily activities stably. Activities are carried out online through WAG media and zoom meetings. Bipolar survivors respond positively and benefit greatly. As many as 64.86% of survivors admitted that they understood the education delivered very well, and as many as 5.4% admitted that they did not understand because education used online media so that it was less focused. Overall, bipolar survivors can realize the importance of taking medication, stabilize emotions and moods and learn to communicate effectively in daily life.